Colorimetric ionophore-based coextraction titrimetry of potassium ions - Kajorngai Thajee (2018)
© 2018 Elsevier B.V. Potassium ion concentration can be successfully determined volumetrically by moving the titration from a homogeneous phase to a two phase solvent system. This is because potassium can be readily complexed in a selective and thermodynamically stable manner by ionophores such as valinomycin. Previous work demonstrated the successful titration of potassium by ion-exchange into an organic phase containing valinomycin, but the sample itself served as titrant, which is not sufficiently practical for routine applications. This problem is overcome here by a co-extraction based approach, with the sodium salt of the water soluble lipophilic anion tetraphenylborate as titrant. The extraction of potassium tetraphenylborate must be preferred over that of the hydrogen ion-tetraphenylborate pair, which is used to indicate the endpoint by the presence of a lipophilic indicator in the organic phase. This is controlled by the sample pH, which for the conditions chosen here is around 7 for optimal sharpness and accuracy of the endpoint. The approach is demonstrated in a colorimetric detection approach, by use of a tethered digital camera and subsequent automated analysis of the resulting image files. The potassium analysis in a variety of samples is successfully demonstrated, including blood serum.